Accelerating the software development process through the application of MVP and monolithic architecture - Lima, Rayfran Rocha; Silva, Alexandre Teixeira da (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
CONTEXT: The growing demand for efficiency in software development and rapid value delivery has led organizations to explore diverse architectural and methodological approaches. In particular, adopting Minimum Viable Product (MVP) strategies and monolithic architecture has shown promise in accelerating the development process, especially in environments where resources and time are constrained. GOAL: This paper presents a detailed experience report on the implementation of MVP and monolithic architecture in a software development guild within a global software company. The main objective is to evaluate the impact of these approaches on development speed, team productivity and overall quality of the production of complementary software, which can be reused via API by other systems within the organization. METHOD: The evolution of the architectural and methodological approaches went through three phases, spanning over 18 months, involving the transition from unstructured development practices to standardized MVP and monolithic methodologies. Data were collected through direct observations, document analysis, and interviews with team members and users. RESULTS: MVP and monolithic architecture implementation significantly reduced development time and improved team productivity. The structured approach facilitated better resource management and enabled faster iteration based on user feedback. However, challenges related to system scalability and maintainability were noted. CONCLUSION: The findings suggest that while MVP and monolithic architecture can accelerate the software development process and enhance team efficiency, careful consideration must be given to the long-term implications on system scalability and maintainability.